Divergence of photosynthetic strategies amongst marine diatoms - Fisher, Nerissa L. (PLoS One, 2020)
Marine phytoplankton, and in particular diatoms, are responsible for almost half of all primary production on Earth. Diatom species thrive from polar to tropical waters and across light environments that are highly complex to relatively benign, and so have evolved highly divergent strategies for regulating light capture and utilization. It is increasingly well established that diatoms have achieved such successful ecosystem dominance by regulating excitation energy available for generating photosynthetic energy via highly flexible light harvesting strategies. However, how different light harvesting strategies and downstream pathways for oxygen production and consumption interact to balance excitation pressure remains unknown. We therefore examined the responses of three diatom taxa adapted to inherently different light climates (estuarine Thalassioisira weissflogii, coastal Thalassiosira pseudonana and oceanic Thalassiosira oceanica) during transient shifts from a moderate to high growth irradiance (85 to 1200 μmol photons m(-2) s(-1)). Transient high light exposure caused T. weissflogii to rapidly downregulate PSII with substantial nonphotochemical quenching, protecting PSII from inactivation or damage, and obviating the need for induction of O(2) consuming (light-dependent respiration, LDR) pathways. In contrast, T. oceanica retained high excitation pressure on PSII, but with little change in RCII photochemical turnover, thereby requiring moderate repair activity and greater reliance on LDR. T. pseudonana exhibited an intermediate response compared to the other two diatom species, exhibiting some downregulation and inactivation of PSII, but high repair of PSII and induction of reversible PSII nonphotochemical quenching, with some LDR. Together, these data demonstrate a range of strategies for balancing light harvesting and utilization across diatom species, which reflect their adaptation to sustain photosynthesis under environments with inherently different light regimes.